Use of Castor Oil in Tissue Repair of Extensive Wound in Senile Horse - Peres, Anelise Ribeiro [UNESP]; Melo Junior, Jairo de; Casas, Vitor Foroni; Macente, Beatrice Ingrid [UNESP]; Menegasso Mansano, Cleber Fernando [UNESP] (Univ Fed Rio Grande Do Sul, 2015)
Background: The use of antiseptics to inhibit or destroy microorganisms through synthetic or natural substances helps speed the healing process. Herbal derivatives of ricinoleic acid extracted from castor beans (Ricinus communis), is an important ally in the treatment of wounds of various animal species during the different stages of the healing process. This study investigates the use of a castor oil based ointment as an antiseptic and wound healing agent to treat an extensive lacerating wound in a senile horse. Case: A 17-year-old Quarter Horse presenting laceration located in the region of the semitendinosus and semimembranosus muscles of the right hindlimb. No changes were observed upon clinical examination while the haematological parameters creatine kinase and fibrinogen increased due to changes. The lesion initially was 35 cm long, and 19 cm wide and second intention healing was the treatment of choice after evaluation. The experimental use of the phytotherapic based on castor oil (Ricinus Assept (R)) was suggested. This choice was based on the horse owner request for a low-cost treatment. Following the decision, the treatment started with injury debridement by removing devitalized tissue followed by application of castor oil. This treatment was performed twice a day during 24 weeks, with curettage every 7 days to determine the progress of the healing process. The monitoring of the wound shrinking was performed using a measuring tape. Length and width were measured every seven days, which started on the first day of treatment. In the first week of treatment, there was a significant decrease in purulent secretion, indicating that contamination was subsiding. However, the measurements between the 8th and 9th weeks, after treatment had started, showed the greatest difference in wound length and width. During the 24th week of treatment, the wound was fully recovered, and completely healed, without clinical signs of hypersensitivity to the drug used. After one year, the owner was contacted and reported that the horse did not show any abnormal change where the healing took place and was in perfect health. Discussion: Much of the clinical practice is spent treating accidental wounds and with post-surgery care. To understand the complexity of the wound healing and the effect of chemicals is essential when making decisions about the most appropriate treatment due to the unique healing nature of wounds in horses. Wound healing is a complex sequence of biochemical and physiological events that can be become even more complicated at advanced age. There are, currently, on the market a large number of topical medications for wounds. The use of phytotherapics in inflammatory and regenerative processes is very promising, as evaluated and proven in other studies with Triticum vulgare, Aloe vera, Stryphnodendron bartatimao, Calendula officianalis and Symphitum officinalis. Countless studies show that the medium chain triglycerides, which are also constituents of castor oil, act positively in the healing process. Castor oil has been shown to be an alternative to treat wounds having bactericidal, chemical debridement, healing, repellent and larvicide properties. This study describes the case of an old animal, and age is an important factor when it comes to the healing process of skin wounds. Despite this fact, castor oil was effective to heal an extensive wound, in addition to being easy to apply and low cost, promoting good antisepsis and the healing process.
Keywords: Ricinus communis; horse; healing; Ricinus Assept (R); treatment